Do ponto de vista do sujeito da pesquisa: evento e cultura material em um comitê de ética em pesquisa - Rui Massato Harayama (2011)
In this research we present an ethnography of a Research Ethics Committees (CEP) associated to the CEP-CONEP System. An institution created by the enactment of Resolution CNS 196/96. The description of the CEP is presented with a revision of works in anthropology related to the ascension of research regulatory systems and by the CEP-CONEP System historiography. The last part presents an analysis of the data obtained in fieldwork. With this work, we aim to bring some data and reflection about the Brazilian research ethics regulatory system.